Image Seam Carving Based on Content Aware Resizing by Gradient Method (Al-Mansour Journal, 2022)
In this paper, bilateral filter and seam carving is implemented to get an image that is retargeted to a new size and has a clear appearance. Bilateral filter is used to enhance images by smoothing texture and preserving edges. The implemented seam carving for content aware image resizing gives better results in resizing images than the standard scaling and cropping techniques. Also, six types of edge detection filters are used in this paper to preserve the energy of image objects, and evaluation for these filters is done to find the best energy preserver among those six types.
Keywords: Bilateral filter; Seam Carving; Edge Detection